2021
DOI: 10.3390/v13122469
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Dynamics of Type 2 Porcine Reproductive and Respiratory Syndrome Virus by Whole-Genome Analysis

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV), an important pathogen in the swine industry, is a genetically highly diverse RNA virus. However, the phylogenetic and genomic recombination properties of this virus are not yet fully understood. In this study, we performed an integrated analysis of all available whole-genome sequences of type 2 PRRSV (n = 901) to reveal its evolutionary dynamics. The results showed that there were three distinct phylogenetic lineages of PRRSV in their distribution pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…These data indicated that not only the four reverse mutation sites but also some other sites mutated during in vitro reverse passaging (see Table S2 in the supplemental material) may contribute to the adaptation to PAMs and the reobtained fatal virulence of the viruses. So positive selection site identification ( 41 43 ) and AlphaFold protein structure prediction ( 44 , 45 ) might be used to further screen the candidate sites among the genomes in our future study.…”
Section: Discussionmentioning
confidence: 99%
“…These data indicated that not only the four reverse mutation sites but also some other sites mutated during in vitro reverse passaging (see Table S2 in the supplemental material) may contribute to the adaptation to PAMs and the reobtained fatal virulence of the viruses. So positive selection site identification ( 41 43 ) and AlphaFold protein structure prediction ( 44 , 45 ) might be used to further screen the candidate sites among the genomes in our future study.…”
Section: Discussionmentioning
confidence: 99%
“…We also predicted the structures of the Gp5/M of viruses belonging to four different sublineages of PRRSV-2 [ 61 ]. The results, displayed in Figure S6 , revealed that the folding of each dimer was consistent with the predicted structure of the Gp5/M of VR 2332.…”
Section: Resultsmentioning
confidence: 99%
“…We also predicted the signal peptide cleavage sites of the Gp5 of the representative members of the three clades of the PRRSV-2 strains and their sublineages [ 61 ]. Every Gp5 protein had the main cleavage site between residue 31 and 32, but for 10 of the 15 sequences, a second minor site upstream of the main site was predicted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The original studies mainly focus on the pathogenicity, evolution, and detection of porcine reproductive and respiratory syndrome virus (PRRSV), coronaviruses, and circoviruses, which are the top porcine viruses circulating in China to date [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. As reported, PRRSV regulates the expression of poly- N -acetyllactosamine and complex N -glycan in porcine pulmonary microvascular endothelial cells [ 1 ].…”
mentioning
confidence: 99%